Implementasi Model PBL Berbasis MOOC dalam Mengembangkan Kecerdasan Linguistik dan Logis Pada Pelajaran Matematika - Maulidina, Lailiya Dinda; Anwar, Khoirul (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
His study investigates the enhancement of students' linguistic and logical intelligence in mathematics using a Project-Based Learning (PBL) approach facilitated by the Massive Open Online Course (MOOC) platform. Employing a mixed-methods approach, the research conducted pre-test and post-test assessments alongside qualitative methods such as interviews and class observations. Twenty fourth-grade students from SD Negeri 51 Gresik were purposively sampled. Analysis indicated non-significant results in pre-test and post-test data distribution (p > 0.05), but paired samples t-tests demonstrated a significant increase in learning effectiveness (p = 0.00). Interviews highlighted enhanced collaboration, enjoyment, and comprehension of material using the MOOC-based PBL model. The study concludes that this approach effectively fosters linguistic and logical intelligence in mathematics. The research contributes theoretically and practically to the development of culturally appropriate project-based learning models.